PERAN TENAGA KERJA WANITA DALAM KEGIATAN USAHATANI KACANG TANAH DI DESA KANONANG, KECAMATAN KAWANGKOAN BARAT - Pingkan ., Assa; Ribka M. Kumaat; Paulus A. Pangemanan (Sam Ratulangi University, 2017)
The aim of this research is to know the role of women farmer in peanut farming activity. This research was carried out for two months from May until June 2017. Samples were taken as many as 20 respondents (Survey Sampling), each village was taken 5 respondents: on Kanonang 1 Village, Kanonang 2 Village, Kanonang 4 Village, and Kanonang 5 Village at Kawangkoan Barat District. The data collected in this study through interviews and presented descriptively in tabular form. The role of female laborers is seen from the peak time of women work in peanut farming is highest in weeding activity, second harvest, third post harvest, fourth marketing, fifth planting, six tillage, seventh seed selection. Women are not play role on fertilization and pest control of diseases.